Consistent alteration of chain length-specific ceramides in human and mouse fibrotic kidneys - Eckes, Timon; Trautmann, Sandra; Djudjaj, Sonja; Beyer, Sandra; Patyna, Sammy; Schwalm, Stephanie; Gauer, Stefan; Thomas, Dominique; Schaefer, Liliana; Boor, Peter; Koch, Alexander; Pfeilschifter, Josef (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
Several studies revealed alterations of single sphingolipid species, such as chain length-specific ceramides, in plasma and serum of patients with kidney diseases. Here, we investigated whether such alterations occur in kidney tissue from patients and mice suffering from renal fibrosis, the common endpoint of chronic kidney diseases. Human fibrotic kidney samples were collected from nephrectomy specimens with hydronephrosis and/or pyelonephritis. Healthy parts from tumor nephrectomies served as nonfibrotic controls. Mouse fibrotic kidney samples were collected from male C57BL/6J mice treated with an adenine-rich diet for 14 days or were subjected to 7 days of unilateral ureteral obstruction (UUO). Kidneys of untreated mice and contralateral kidneys (UUO) served as respective controls. Sphingolipid levels were detected by LC-MS/MS. Fibrotic markers were analyzed by TaqMan® analysis and immunohistology. Very long-chain ceramides Cer d18:1/24:0 and Cer d18:1/24:1 were significantly downregulated in both fibrotic human kidney cortex and fibrotic murine kidney compared to respective control samples. These effects correlate with upregulation of COL1α1, COL3α1 and αSMA expression in fibrotic human kidney cortex and fibrotic mouse kidney. We have shown that very long-chain ceramides Cer d18:1/24:0 and Cer d18:1/24:1 are consistently downregulated in fibrotic kidney samples from human and mouse. Our findings support the use of in vivo murine models as appropriate translational means to understand the involvement of ceramides in human kidney diseases. In addition, our study raises interesting questions about the possible manipulation of ceramide metabolism to prevent progression of fibrosis and the use of ceramides as potential biomarkers of chronic kidney disease. •Very long-chain ceramides are downregulated in fibrotic renal tissue.•Regulation of ceramides in fibrotic kidneys is similar in mice and men.•Different ceramide profile in human renal cortex compared to renal medulla